2004
DOI: 10.1029/2003wr002355
|View full text |Cite
|
Sign up to set email alerts
|

Development of effective and efficient rainfall‐runoff models using integration of deterministic, real‐coded genetic algorithms and artificial neural network techniques

Abstract: [1] Many researchers have reported about the problems in modeling low-magnitude flows while developing artificial neural network (ANN) rainfall-runoff models trained using popular back propagation (BP) method and have suggested the use of alternative training methods. This paper presents the results of a new approach employing real-coded genetic algorithms (GAs) to train ANN rainfall-runoff models, which are able to overcome such problems. The paper also presents a new class of models termed gray box models th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(103 citation statements)
references
References 32 publications
0
103
0
Order By: Relevance
“…Table 1 summarizes the quantitative performance indices employed in this study. Details on the indices can be found in Jain and Srinivasulu [31] for the effectiveness indices and Dawson et al [77] for efficiency indices, respectively. CE, r 2 , IOA, and PI are dimensionless indices.…”
Section: Quantitative Performance Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the quantitative performance indices employed in this study. Details on the indices can be found in Jain and Srinivasulu [31] for the effectiveness indices and Dawson et al [77] for efficiency indices, respectively. CE, r 2 , IOA, and PI are dimensionless indices.…”
Section: Quantitative Performance Indicesmentioning
confidence: 99%
“…R4MS4E is a good efficiency index for high and peak flows and has the same unit as original data [77,78]. AARE and TS give appropriate weights for low, moderate, and high flows, and it has been reported that they can provide better performance evaluation [31]. …”
Section: Quantitative Performance Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…R is an index commonly used to describe the correlation of two series. AARE can measure the error between the observation and simulated data [34]. In general, high NSE and R values and small AARE values indicate good modeling performance.…”
Section: Discrete Wavelet Transform and Modeling Designmentioning
confidence: 99%
“…average daily effective 846 rainfall: P(t), P(t-1) and average daily runoff: Q(t-1), Q(t-2)) (Galelli et al, 2014; Jain and 847 Srinivasulu, 2004). For this case study, the effectiveness of PMI IVS is investigated by 848 introducing another 17 redundant or irrelevant candidate inputs, as shown in Table 6.…”
mentioning
confidence: 99%